Calculus, 10th Edition (Anton)

Published by Wiley
ISBN 10: 0-47064-772-8
ISBN 13: 978-0-47064-772-1

Chapter 1 - Limits and Continuity - 1.2 Computing Limits - Exercises Set 1.2: 7

Answer

4

Work Step by Step

$x^{4}$ - 1 = (x - 1)(x³ + x² + x + 1), so: $\frac{x^{4}-1}{x-1}$ = x³ + x² + x + 1. Now we have: $\lim\limits_{x \to 1^{+}}\frac{x^{4}-1}{x-1}$ = $\lim\limits_{x \to 1^{+}}x³ + x² + x + 1$ = 1³ + 1² + 1 + 1 = 4
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.